2011
DOI: 10.1186/1297-9716-42-112
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of group A rotaviruses associated with repeated outbreaks of diarrhea in a farrow-to-finish farm: identification of a porcine rotavirus strain bearing a novel VP7 genotype, G26

Abstract: Group A rotaviruses (GARs) are one of the most common causes of diarrhea in suckling pigs. Although a number of G and P genotypes have been identified in porcine GARs, few attempts have been made to study the molecular epidemiology of these viruses associated with diarrhea outbreaks within a farm over an extended period of time. Here, we investigated the molecular characteristics of GARs that caused four outbreaks of diarrhea among suckling pigs in a farrow-to-finish farm over the course of a year. G and P gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 37 publications
3
34
0
3
Order By: Relevance
“…Out of 200 suspected field samples from piglets, calves and children, the overall prevalence of RV was found to be higher in piglets followed by humans and calves. Overall, RVAs were detected more recurrently and is consistent with the earlier reports [10,12,19,21]. Past studies [23] from the valley, solely on pigs also confirmed piglet RV prevalence.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Out of 200 suspected field samples from piglets, calves and children, the overall prevalence of RV was found to be higher in piglets followed by humans and calves. Overall, RVAs were detected more recurrently and is consistent with the earlier reports [10,12,19,21]. Past studies [23] from the valley, solely on pigs also confirmed piglet RV prevalence.…”
Section: Discussionsupporting
confidence: 90%
“…Rotavirus (RV) infections are the leading cause of neonatal diarrhea and are worldwide in distribution causing high morbidity and mortality in humans, animals and birds [1,4,14,21]. Among all serogroups, rotaviruses belonging to group A are predominant cause of severe gastroenteritis [4,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the outer capsid VP4 (P genotype)-and VP7 (G genotype)-encoding genes, a binary classification system has been established for RVs (12). Overall, there are at least 26 G genotypes and 33 P genotypes of group A RVs (RVAs) (13,14). Globally, the G1 to G4, P[4], P[6], and P [8] genotypes are the most prevalent human RVAs (15).…”
Section: Importancementioning
confidence: 99%
“…According to this scheme, 27 G and 35 P genotypes have been described for RVAs of humans and animals (27). To date, 12 G genotypes (G1 to G6, G8 to G12, and G26) and 13 P genotypes (P [1], P [5] to P [8], P [11], P [13], P [19], P [23], P [26], P [27], P [32], and P [34]) have been detected in pigs (5,16,23,25,27,34,37).…”
mentioning
confidence: 99%